The Effects of Water Consumption on Biometry in Myopic Young Adults - As'ari, Amirah Irdina; Che Mohd Zain, Nureen Syaza; Abdul Rahim, Muhammad Afzam Shah; Mohamad Shahimin, Mizhanim; Subri, Sabrina; Yusof, Firdaus (International Journal of Allied Health Sciences, 2025)
Background: Myopia, characterized by excessive axial elongation and altered scleral biomechanics, is associated with an increased risk of ocular morbidity. Although axial length (AL) measurement is crucial for monitoring myopia progression, its stability under physiological stressors such as water ingestion remains uncertain. The water drinking test (WDT) transiently elevates intraocular pressure (IOP) and could potentially deform ocular structures, particularly in eyes with reduced scleral compliance. This study investigated the acute effects of water consumption on ocular biometry; AL, central corneal thickness (CCT), anterior chamber depth (ACD), and lens thickness (LT) in myopic and emmetropic young adults. Methods: Thirty-two healthy participants (15 emmetropes, 17 myopes; aged 18–25 years) underwent standardized WDT involving ingestion of 100 mL of water per 10 kg of body weight. Biometric parameters were measured at baseline and at 5, 15, 30, and 45 minutes post-ingestion using Lenstar optical biometry (Haag-Streit, Switzerland). Data were analyzed using appropriate parametric and non-parametric tests, with p < 0.05 considered statistically significant. Results: AL remained stable in myopes (F(4,64)=1.678, p=0.166) but showed a modest time effect in emmetropes (?²(4)=10.354, p=0.035). Myopes exhibited consistently longer AL than emmetropes across all time points (p<0.05). LT showed a time effect in emmetropes (p=0.004) without significant pairwise changes. No significant alterations were observed for CCT or ACD in either group. Conclusion: Acute systemic hydration did not significantly affect ocular biometry in myopic young adults, supporting the reliability of single-timepoint measurements for clinical monitoring. The persistent AL disparity between groups highlights inherent structural differences in ocular biomechanics independent of short-term hydration.